Welcome to attend 2013 Society for Engineering in Agriculture (SEAg 2013) Conference in Western Australia - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
2013 Society for Engineering in Agriculture (SEAg 2013) Conference featured with the theme of “Innovative Agricultural Technologies for a Sustainable Future” will be co-sponsored by Engineers Australia (EA), Society for Engineering in Agriculture (SEAg) and International Commission of Agricultural and Biosystems Engineering (CIGR). The SEAg 2013 Conference will be held at the Atrium Hotel located less than an hour south of Perth in Mandurah, Western Australia's metropolitan coastal getaway destination on September 22-25, 2013 and includes a one day post conference tour to the irrigation, horticultural and cereal cropping farm machinery used in the southern areas of Western Australia. Australia is a country of great diversity with extreme agricultural challenges. Innovation has been a prerequisite for the agricultural sector. This conference provides a unique forum for local and international delegates to network and share ideas on how we can provide innovative solutions for sustainable food and fiber production in the future. In order to reduce the travel costs and registration fees, and to provide a better and convenient communication platform, the editorial office of International Journal of Agricultural and Biological Engineering (IJABE, www.ijabe.org) will organize a Chinese delegation to attend the SEAg 2013 Conference. We therefore invite you to join us to participate in the SEAg 2013 Conference. The conference deals with the challenges faced by the agricultural sector related to a range of economic, environmental and social factors and where research, development and adoption of new agricultural technologies provide real opportunities in innovative solutions for sustainable agricultural production systems of the future. Website: www.engineersaustralia.org.au/2013-society-engineering-agriculture-conference